Weed emergence in autumn under temperate conditions - Calado,J.M.G. (2011)
The emergence of weed plants depends on environmental conditions, especially temperature and soil moisture. The latter is extremely important in Mediterranean environments which are characterized by irregular amount and distribution of rain throughout the year, which influences the beginning of the growth cycle of the annual species (seed germination). This paper studies the influence of rainfall, in particular accumulated rainfall in autumn, on the emergence of weed plants. The experiment was carried out on Luvisols, and the appearance of flora under field conditions was observed. Through analysis of the results, it can be concluded that a high percentage of weed plants (> 85% related to the highest registered value) was obtained with more than 90 mm of accumulated rainfall from the beginning of September. Thus, in those years in which this amount of rainfall (90 mm) is registered until the end of October, the appearance of potential weed plants can be ensured, under Mediterranean conditions, in a period before sowing the autumn-winter crops.